Transforming Pedagogical Competence Through Structured Module Development Training - Siagian, Iin Adelorinta; Mumpuniarti, Mumpuniarti (Journal of Innovation and Research in Primary Education, 2025)
The rapidly evolving educational landscape demands continuous enhancement of teacher pedagogical competence, yet significant gaps remain in teachers' abilities to develop comprehensive instructional modules. This quasi-experimental study with one-group pretest-posttest design investigated the impact of instructional module development training on elementary school teachers' pedagogical competence. Forty-five elementary school teachers in Pangandaran Regency participated in a four-week intensive training program aligned with the Merdeka Curriculum framework. Data were collected using a validated pedagogical competence assessment instrument (α = 0.89) measuring four dimensions: instructional planning, teaching methodology, classroom management, and assessment practices. Paired-samples t-test and descriptive statistics were employed for data analysis. The training intervention produced statistically significant improvements in overall pedagogical competence, with mean scores increasing from 2.87 to 4.21 (t(44) = 18.76, p < 0.001, Cohen's d = 3.42). The most substantial improvement occurred in instructional planning and design (64.15%), followed by teaching methodology (44.64%), assessment practices (42.47%), and classroom management (37.42%). Post-training, 86.7% of teachers achieved high or very high competence levels compared to only 13.4% pre-training. These findings demonstrate that structured, intensive training in module development effectively enhances multiple dimensions of pedagogical competence, particularly benefiting teachers with lower initial capabilities. The results have important implications for designing evidence-based professional development programs that produce sustainable improvements in teacher quality.